Na2SO4 + Fe(NO3)3 → Fe2(SO4)3 + Pb(NO3)2→ KOH + H2SiO3 → С коэффициентами, полное ионное уравнение

Na2SO4 + Fe(NO3)3 → Fe2(SO4)3 + Pb(NO3)2→ KOH + H2SiO3 → С коэффициентами, полное ионное уравнение
Гость
Ответ(ы) на вопрос:
Гость
3Na2SO4 + 2Fe(NO3)3 = 6NaNO3 + Fe2(SO4)36Na(+) + 3SO4(-2) + 2Fe(+2) + 6NO3(-) = 6Na(+) + 6NO3(-) + 2Fe(+3) + 3SO4(-2)Реакция не идётFe2(SO4)3 + 3Pb(NO3)2 = 2Fe(NO3)3 + 3PbSO42Fe(+3) + 3SO4(-2) + 3Pb(+2) + 6NO3(-) = 2Fe(+3) + 6NO3(-) + 3PbSO43Pb(+2) + 3SO4(-2) = 3PbSO42KOH + H2SiO3 = K2SiO3 + 2H2O2K(+) + 2OH(-) + H2SiO3 = 2K(+) + SiO3(-2) + 2H2O2OH(-) + H2SiO3 = SiO3(-2) + 2H2O
Не нашли ответ?
Ответить на вопрос
Похожие вопросы